EVALUATING AUTHENTICITY OF CRAFT AND CRAFTMANSHIP IN THE INDIAN CRAFTS - Singh, Harminder; Brar, Tejwant; Dat, Sachin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The handicraft industry’s expansion has been hindered by several factors, including the lack of awareness and training among craftspeople and their inability to command higher prices for their products based on the unique selling proposition of being "Hand Crafted." These craftsmen’s ability to charge premium rates was further hindered by competition from comparable products offered in other areas or nations that unfairly profited from the reputation of these distinctive products but discounted the inherent authenticity of the craft. The artisans felt that there was no future for them because they could not support their families with their crafts, which demotivated them. Nonetheless, artisans can set fair pricing for their authentic goods since they can prevent piracy by exercising their IPRs to the fullest extent possible. The craftspeople must also recognise that standards for quality and how they are measured might vary across time and space. Goods that were legal in the past are now prohibited. For instance, ivory, which was once widely utilised, is now completely banned. Similar to how certain nations forbid the use of plastic, many other limitations and encumbrances are enforced globally. It has been difficult for the craftspeople to stay up to date. In several global rejections of handicraft products, the lack of the stamp of authenticity makes these goods likely to be rejected. Artisans need to reconcile to the fact that there is an urgent need to recognise the accurate picture where cheap imitations are challenging their genuine articles. They need to take cognisance of the fact that they should be agreeable to putting their items through extensive testing and inspection processes to determine their quality so that they can obtain the accurate valuation and cost for their hard work and their exquisite artistry in turning out such breathtakingly beautiful works of craftsmanship for posterity.